A Urease-Catalyzed Three-Component Reaction for the Efficient and Sustainable Synthesis of Highly Substituted 4H-Pyrans in Water as the Solvent - Saleh, Mahmoud Abo El Makarim; Conrad, Jürgen; Frey, Wolfgang; Beifuss, Uwe (Synthesis, 2024)
An efficient urease-catalyzed approach for the synthesis of highly substituted 6-amino-4H-pyran-3-carbonitriles based on the formation of three bonds in one step is developed. This unprecedented three-component reaction between one molecule of an aromatic aldehyde and two molecules of an aroylacetonitrile proceeds by employing commercially available urease from jack bean (Canavalia ensiformis) as the catalyst in water at 65 °C to deliver the desired 4H-pyrans in yields of up to 92%. The transformation is proposed to occur via a domino Knoevenagel condensation/1,4-addition/O-cyclization/tautomerization sequence, providing a practical and sustainable approach to 6-amino-4H-pyran-3-carbonitriles from commercially available substrates. Full and unambiguous structural elucidation of all the products is achieved by means of NMR spectroscopy and X-ray crystal structure analysis.
Keywords: heterocycles; 4H-pyrans; multicomponent reaction; biocatalysis; enzymes; urease; green chemistry